2022
DOI: 10.56578/ataiml010103
|View full text |Cite
|
Sign up to set email alerts
|

House Price Prediction Using Exploratory Data Analysis and Machine Learning with Feature Selection

Abstract: In many real-world applications, it is more realistic to predict a price range than to forecast a single value. When the goal is to identify a range of prices, price prediction becomes a classification problem. The House Price Index is a typical instrument for estimating house price discrepancies. This repeat sale index analyzes the mean price variation in repeat sales or refinancing of the same assets. Since it depends on all transactions, the House Price Index is poor at projecting the price of a single hous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Pre-processing is one of the important stages in data analysis which often improves the quality of the results of a method [12][13][14][15][16]. In cluster analysis, pre-processing can be done with transformations to standardize data [12,13,16].…”
Section: Transformation Methods and Proximity Measurementioning
confidence: 99%
“…Pre-processing is one of the important stages in data analysis which often improves the quality of the results of a method [12][13][14][15][16]. In cluster analysis, pre-processing can be done with transformations to standardize data [12,13,16].…”
Section: Transformation Methods and Proximity Measurementioning
confidence: 99%
“…In this study, we apply the suggested model to the UCF-Crime dataset [23], which contains a large amount of footage from public surveillance cameras documenting anomalous, unlawful, and violent behaviour in settings as diverse as schools, businesses, and streets. This dataset was chosen because its events are representative of those that occur often and in a variety of settings [24][25][26]. Furthermore, these aberrant behaviours can cause significant issues for both people and society.…”
Section: Datasetmentioning
confidence: 99%
“…Although not all solvers support all penalty types, the type of penalty may be chosen through the "penalty" parameter with values of "l1", "l2", or "elasticnet" (e.g., both). The "C" option allows the penalty's coefficient weighting to be modified [23].…”
Section: Logistic Regression (Lr)mentioning
confidence: 99%